2006
DOI: 10.1158/0008-5472.can-05-1145
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Human Prostate Cancer by Oral Administration of Green Tea Catechins in Volunteers with High-Grade Prostate Intraepithelial Neoplasia: A Preliminary Report from a One-Year Proof-of-Principle Study

Abstract: Green tea catechins (GTCs) proved to be effective in inhibiting cancer growth in several experimental models. Recent studies showed that 30% of men with high-grade prostate intraepithelial neoplasia (HG-PIN) would develop prostate cancer (CaP) within 1 year after repeated biopsy. This prompted us to do a proof-of-principle clinical trial to assess the safety and efficacy of GTCs for the chemoprevention of CaP in HG-PIN volunteers. The purity and content of GTCs preparations were assessed by high-performance li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
526
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 740 publications
(537 citation statements)
references
References 32 publications
6
526
0
5
Order By: Relevance
“…Nevertheless, clinical evidence is scarce and provides conflicting results for the effects of these compounds. In a double-blind placebo-controlled study, green tea catechins (GTC) significantly prevented prostate cancer development in men with highgrade premalignant prostate intraepithelial neoplasia (42). Two randomized, double-blind, placebo-controlled short-term isoflavone intervention trials before radical prostatectomy have shown that genistein failed to change the PSA levels significantly, even though it modulated the expression of several genes involved in prostate cancer (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, clinical evidence is scarce and provides conflicting results for the effects of these compounds. In a double-blind placebo-controlled study, green tea catechins (GTC) significantly prevented prostate cancer development in men with highgrade premalignant prostate intraepithelial neoplasia (42). Two randomized, double-blind, placebo-controlled short-term isoflavone intervention trials before radical prostatectomy have shown that genistein failed to change the PSA levels significantly, even though it modulated the expression of several genes involved in prostate cancer (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Although a phase 2 clinical trial of DFMO with patients with a family history of prostate cancer but no previous personal history of prostate cancer has been reported, 55 no trials have included patients with a diagnosis of HGPIN and no evidence of prostate cancer. Different chemopreventive clinical trials have been developed to control progression of HGPIN to prostate cancer using selenium, soy, vitamin E, 56,57 toremifene, 58 or green tea extract, 59,60 with different success rates. Our findings suggest that DFMO treatment, which is usually associated with minimal toxicity, 61 may prove valuable for reducing the development of prostate cancer in patients with a diagnosis of HGPIN and may play a crucial role in future chemopreventive clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The use of phytonutrient as anticancer agents has gained considerable importance in recent years. Several studies from our laboratory and by others have suggested that green tea, especially its constituent polyphenols possess chemopreventive and therapeutic potential against CaP (Jian et al, 2004;Bettuzzi et al, 2006;Siddiqui et al, 2006Siddiqui et al, , 2007. Much of the anticancer and/or cancer chemopreventive effects of green tea are attributed to be mediated by its major polyphenol(À)epigallocatechin-3-gallate (EGCG) ; and the references therein).…”
Section: Introductionmentioning
confidence: 99%